Determinants Influencing the Decision to Use the ShopeePay Digital Wallet in Generation Z in North Bekasi City - Muhammad Richo Rianto; Fadhilah, Farras (Kirana Publisher (KNPub), 2023)
The research's main objective is to measure the decision of generation Z in North Bekasi City to use the ShopeePay digital wallet which is influenced by financial literacy, perceived benefits, perceived convenience, and income. This study used quantitative methods with purposive sampling techniques and a total sample of 145 respondents. Using the structural equity model (SEM) – SmartPLS 4.0. The results of this study provide an explanation that the variables perceived benefits, perceived convenience, and income have a positive effect on the decision to use the ShopeePay digital wallet in generation Z in North Bekasi City. However, the financial literacy variable has no effect on the decision to use the ShopeePay digital wallet.